Integrated management protocol for New Zealand endemic wheat bug (Nysius huttoni) in forage brassicas - Tiwari, S.; Dickinson, N.; Wratten, S. D. (Journal of Agriculture and Forestry University, 2020)
Wheat bug, Nysius huttoni, is considered as an economic pest of forage Brassicas and many other cultivated crops, such as wheat, kale, and vegetables in New Zealand. Insecticides- as seed coatings and sprays are frequently used to manage this pest, but a high proportion of these insecticidal compounds enter the soil and leads to pesticide resistance, and they may impact beneficial arthropods and soil microorganisms, creating an adverse effect on ecosystem services (ES). In this paper, we discuss a technology, that we have developed to trap , for example, wheat bug away from kale seedlings, and integrating these in less susceptible kale cultivars that can potentially reduce over-reliance on orthodox pesticides on brassicas. Laboratory studies were conducted to screen the suitable trap crop among nine other plants (alyssum, wheat, phacelia, buckwheat, coriander, white clover, alfalfa, and kale) mainly by considering growth stages (vegetative and flowering), and select less susceptible kale cultivars among six other (Kestrel, Gruner, Sovereign, Regal, Corka and Colear). Alyssum (Lobularia maritima) and wheat (Triticum aestivum) were the most favoured potential trap plants for the wheat bug in a laboraotry study. Flowering stage of alyssum is the most susceptible growth stage by the bug damage. Kestrel and Coleor are the most popular kale cultivars used as forage brassicas in New Zealand, but they are the most susceptible to the wheat bug. Corka and Regal were the least susceptible cultivars. The integration of trap cropping technology by using alyssum as the trap crop, preferably depolying flowering stage, along with sowing less susceptible kale cultivars such as Corka and Regal in main fields have been suggested to protect brassica seedlings from bug damage.